تأثير غازات الاحتراق على تآكل السطوح الخارجية لأنابيب المسخنات الاسترجاعية لمياه التغذية في محطة القوى بمصفاة بانياس. - المحمد موسى (Latakia University Journal -Engineering Sciences Series, 2019)
تعاني المسخنات الاسترجاعية لمياه تغذية المراجل في محطة القوى بمصفاة بانياس من التآكل الناتج عن تأثير غازات الاحتراق على أنابيب هذه المسخنات بسبب المحتوى السيئ للغازات من ملوثات ضارة ( كبريت, فاناديوم...) . يتضمن البحث عرضاً للملوثات الضارة ومجال تأثيرها فضلاً عن وصف للظروف التشغيلية والوقود المستخدم والعلاقة بينها, كما يعرض البحث نتائج لعملية ملاءمة ظروف الاحتراق مع الوقود المستخدم ونتائج استخدام إضافات لتقليل الأثر السلبي لغازات الاحتراق ونتائج تجربة تعديل دارة العمل لتقليل التآكل. يؤكد البحث الاستمرار في استخدام الإضافات الفعالة والاقتصادية وتعديل دارة العمل لتتلاءم مع الواقع التشغيلي الفعلي. The recuperative heater of Banias refinery is suffering from corrosion resulting from the impact of the combustion gases on the pipes of these economizers because of harmful pollutants in the fuel gases (sulfur, vanadium, etc.). This research includes a presentation of the harmful pollutants and the sphere of their influence as well as a description of the operation conditions and the fuel used in the combustion process and the relationship between all. The research displays the results of the appropriate conditions of combustion with the used fuel and the results of the use of addenda to reduce the bad impact of the combustion gases and the results of an experiment to modify the circuit to reduce corrosion. The research emphasizes the continuation of using the effective economic addenda in addition to modifying the work circuit to fit the actual operational realities.